APPLICATION OF THE ITERATIVE MODEL IN DESIGNING AN ACADEMIC E-COUNSELING SYSTEM AT BINA DARMA UNIVERSITY - Megawaty Ipan; Tri Oktarina (Jurnal Teknik Informatika (Jutif), 2023)
Bina Darma University does not yet have a system for guidance on final assignments, theses, theses so that the mentoring process becomes hampered. Problems are caused by several factors, namely conditions, distance, different schedules between lecturers and students. coupled with the current pandemic conditions, the implementation of online lectures so that the guidance process is not optimal, the mentoring history is not well documented, and the most common thing encountered in the field is that students cannot submit complaints related to academic activities. The purpose of this research is to build a student academic e-counseling system at Bina Darma University. The benefits obtained from research are that the guidance/counseling process can run smoothly even though the supervisor does not meet directly with the students, the guidance history data is well documented and coordinated. Become a forum for students in delivering and consulting with their lecturers. The research method uses a descriptive method while the system development method in this study is the iterative model method. the stages of this method are planning, analysis, design, implementation, Maintenance. The results of this study are in the form of student e-counseling systems such as final assignments, theses, and theses. Where this system can manage title submission data, guidance, virtual guidance, student data, supervisor data. Can be accessed online by lecturers and students anytime and anywhere.